2012
DOI: 10.1103/physrevlett.109.215001
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Driven Shock Acceleration of Monoenergetic Ion Beams

Abstract: We show that monoenergetic ion beams can be accelerated by moderate Mach number collisionless, electrostatic shocks propagating in a long scale-length exponentially decaying plasma profile.Strong plasma heating and density steepening produced by an intense laser pulse near the critical density can launch such shocks that propagate in the extended plasma at high velocities. The generation of a monoenergetic ion beam is possible due to the small and constant sheath electric field associated with the slowly decre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
209
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(220 citation statements)
references
References 42 publications
10
209
0
1
Order By: Relevance
“…We have followed the field evolution in 2D and 3D simulations and showed that a quasi-steady-state value is reached, with the magnetic field being generated only in the downstream region, in contrary to electromagnetic shocks where the filamentation instability creates a magnetic field across the shock front. We have observed that since the field is generated in the downstream region, the effect of the selfgenerated magnetic field on the formation process is negligible, and the properties of the electrostatic shock, e.g., in terms of ion reflection, are preserved [7,8,42]. On the other hand, the strong field in the downstream region influences the dynamics of the particles in this region, and it can lead to distinct signatures of the shock.…”
Section: -2mentioning
confidence: 96%
See 1 more Smart Citation
“…We have followed the field evolution in 2D and 3D simulations and showed that a quasi-steady-state value is reached, with the magnetic field being generated only in the downstream region, in contrary to electromagnetic shocks where the filamentation instability creates a magnetic field across the shock front. We have observed that since the field is generated in the downstream region, the effect of the selfgenerated magnetic field on the formation process is negligible, and the properties of the electrostatic shock, e.g., in terms of ion reflection, are preserved [7,8,42]. On the other hand, the strong field in the downstream region influences the dynamics of the particles in this region, and it can lead to distinct signatures of the shock.…”
Section: -2mentioning
confidence: 96%
“…Collisionless shocks have been studied for many decades, mainly in the context of space and astrophysics [1][2][3][4]. Recently, shock acceleration raised significant interest in the quest for a laser-based ion acceleration scheme due to an experimentally demonstrated high beam quality [5][6][7][8].Interpenetrating plasma slabs of hot electrons and cold ions are acting to set up the electrostatic fields via longitudinal plasma instabilities. The lighter electrons leaving the denser regions are held back by the electric fields, which pull the ions.…”
mentioning
confidence: 99%
“…Ions within the bulk plasma can be reflected from this shock up to twice the shock velocity, dissipating the energy of the shock. Fiuza et al (2012) demonstrates the possibility of achieving narrowenergy spreads through this mechanism. Both hole-boring and shock acceleration are the reflection of ions from a moving potential generated either directly via radiation pressure, or indirectly driven by the laser via electron heating.…”
Section: Introductionmentioning
confidence: 99%
“…During last fifteen years, different mechanisms for ion acceleration have been suggested and extensively studied, such as target normal sheath acceleration (TNSA) [7,8], collisionless shock acceleration [9][10][11][12], coulomb explosion, break-out afterburner (BOA) [13], and radiation pressure acceleration (RPA) [14][15][16][17][18][19] and so on.…”
Section: Introductionmentioning
confidence: 99%